In Silico Targeting of the Long Noncoding RNA MALAT1 - François-Moutal, Liberty (ACS Med Chem Lett, 2021)
[Image: see text] RNA targeting has gained traction over the past decade. It has become clear that dysregulation of RNA can be linked to many diseases, leading to a need for new scaffolds recognizing RNA specifically. Long noncoding RNAs are emerging as key controllers of gene expression and potential therapeutic targets. However, traditional targeting methods have overwhelmingly been focused on proteins. In this study, we used a protein computational tool and found several possible targetable pockets in a structurally characterized long noncoding RNA, MALAT1. Screening against those identified pockets revealed several hit compounds. We tested the binding of those compounds to MALAT1 RNA and tRNA as a negative control, using SPR. While several compounds were nonspecific binders, others were able to recognize MALAT1 specifically. One of them, MTC07, has an apparent affinity of 400.2 ± 14.4 μM. Although it has weak affinity, MTC07 is the first compound targeting MALAT1 originating from in silico docking.